Uji Viabilitas Benih Melon (Cucumis melo L.) Pada Berbagai Taraf Waktu Penyimpanan Buah dan Pengeringan Biji - Herna Nur Fajrina; Kuswanto Kuswanto (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2019)
Melon (Cucumis melo L.) is one of the fruits of the family Cucurbitaceae, which propagated generatively by seeds. High quality of seed can results plants that good production. The problems often encountered in the seed production technology is the aspect of the post-harvest handling. On melon seed production, seed quality deterioration occurs caused fruit storage and seed drying are less precise. To get high quality seeds, then to do a proper post harvest handling. The purpose of this study is to get the proper time of fruit storage and seed drying to produce the high quality melon seed. The study was conducted from January to March 2018 at PT. BISI International Tbk Farm Karangploso Malang, prepared using Factorial Random Block Design (RCBD). The first factor is the fruit storage time (C), consisting of C1: 1 day, C2: 4 days, C3: 7 days, and C4: 10 days. While the second factor is seeds drying time (K), consisting of K1: 1 day, K2: 2 days, K3: 3 days, and K4: 4 days. Observations were made on the qualitative and the quantitative character including yield of seed result, the weight of 1000 grain, seed water content, seed germination, and seed germination rate. The results showed that there was interaction between fruit storage time treatment and seeds drying time on germination rate variable, while the effect given by each treatment showed a real result on all observation variables.